Conference proceedings (2024)
A low cost meter was developed as part of a USAID funded Feed the Future project headquartered at Kansas State University to reduce post-harvest loss (PHL) of grains and is referred to as the PHL moisture meter. It actually measures the temperature (T) and relative humidity (RH) of the air space between grain kernels and calculates the equilibrium moisture content (EMC) to determine grain moisture. The meter was built and evaluated in laboratory studies in the U.S. and field tested in Ghana and Nigeria. Meter accuracy was compared to two commercial meters: (a) John Deere Chek Plus-SW08120 grain moisture tester and (b) bench top DICKEY-john GACO2100 Agri meter. The portable JD meter is a low cost meter by developed country standards (~US$250, 2016 price), whereas the GAC2100 benchtop moisture meter is a USDA-GIPSA-approved tester that is highly regarded in the US grain trade and has been used for many years. Laboratory studies indicated that the PHL moisture meter requires approximately six minutes to make a measurement due to the time required for the probe tip and sensor to equilibrate to the air within the grain mass. Field tests have shown the accuracy of the PHL moisture meter was comparable to that of the GAC2100 moisture meter for maize below 15% MCwb. Measurement differences averaged over many readings showed a positive offset of 0.45% for the PHL meter relative to the GAC2100, whereas the John Deere SW08120 moisture meter was found to have an offset of 2.37% MCwb.